2022
DOI: 10.3390/nu14051034
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Lifestyle Modifications on Alterations in Lipid and Glycemic Profiles and Uric Acid Values in a Pediatric Population

Abstract: Cardiometabolic risk factors are frequent in children and adolescents with excess weight. The aim of this study was to evaluate the effects of lifestyle modifications on alterations in lipid and glycemic profiles and uric acid values in a pediatric population at increased cardiovascular risk. The study involved 276 subjects with a mean age of 10.6 (2.3) years. Body mass index (BMI) z-score and biochemical parameters (serum low-density lipoprotein (LDL) cholesterol, triglycerides and uric acid and homeostasis m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…A randomized study showed beneficial effects on body weight associated with insulin resistance improvement in overweight children undergoing dietary treatment [ 34 ]. Moreover, in our previous study, we observed that the factor most strongly associated with improved insulin resistance values in a pediatric population undergoing a dietary-behavioral intervention was the decrease in BMI z-score [ 11 ]. In the present study, the greater the weight reduction during follow-up, the greater the decrease in systolic blood pressure, and this effect appeared totally mediated by the amount of reduction in insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A randomized study showed beneficial effects on body weight associated with insulin resistance improvement in overweight children undergoing dietary treatment [ 34 ]. Moreover, in our previous study, we observed that the factor most strongly associated with improved insulin resistance values in a pediatric population undergoing a dietary-behavioral intervention was the decrease in BMI z-score [ 11 ]. In the present study, the greater the weight reduction during follow-up, the greater the decrease in systolic blood pressure, and this effect appeared totally mediated by the amount of reduction in insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we described that non-pharmacological treatment based on lifestyle modifications was associated with a reduction in BP, BMI and WC values in a pediatric population with excess weight and/or elevated BP values [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This dietary approach implies different ranges of energy restriction, depending on age target, and a macronutrient distribution approximately equals to 50–60%En from CHO, 15–20%En from proteins and <30%En from fats [ 130 ]. Several clinical trials have been reporting the positive effects of this approach on several indicators of glucose metabolism, including HOMA-IR, insulin levels, adiponectin, and resistin, in children and adolescents with obesity [ 134 , 135 , 136 ].…”
Section: Nutritional Strategies For Modulation Of Insulin Resistancementioning
confidence: 99%
“…when there are risk factors for CVD keeping track of healthy eating habits is critical [37]. Moreover, weight loss and lifestyle modification (healthy food and physical activity) are the most common advice for improving insulin sensitivity [38].…”
Section: Lifestyle Modificationmentioning
confidence: 99%